PERBANDINGAN KARAKTERISTIK SHOVEL SHAPE GIGI INSISIVUS PERTAMA RAHANG ATAS PADA SUKU DI KALIMANTAN (Studi Identifikasi Morfologi Gigi antara Suku Dayak Bukit, Suku Dayak Ngaju dan Suku Banjar Hulu) - Siti Rachmatiara D. Destiarini; Irnamanda DH; Iwan Aflanie (FKG Unlam, 2017)
Backgrounds: Borneo island is inhabited by various tribes such as the Dayak Bukit, Dayak Ngaju and Banjar Hulu. According to Radam (1987) and Tjilik Riwut (1979) these tribes have similarities based on theory of its origins, so the role of identification is required to distinguish people between the invidual in these tribes. Primary identification using dental morphology,one of themis shovel shape which is shown on palatal surface of incisors. Purpose: The research aimed to compare the characteristics of shovel shape maxillary first incisors among some tribes in Borneo. Methods: This research is an analytic observational study with cross sectional design, using dental casts of 156 people that consisting of 52 people Dayak Bukit, 52 people of Dayak Ngaju, and 52 people of Banjar Hulu. Shovel shape of maxillary first incisors observed with score created by Herdlicka (1920). Results: The results showed that the most characteristic shape shovel on Dayak Bukit and Dayak Ngaju are 2 (semi shovel) and Banjar Hulu is 1 (trace shovel). Data were analyzed using Chi-Square test with p=0,0001(p <0.05) indicate a difference in the shovel shape of maxillary first incisors among Dayak Bukit, Dayak Ngaju Dayak, and Banjar Hulu, then performed the Chi-Square test on each of two tribes to describe the comparison between tribes which have differences. Conclusion: Based on the comparison of shape shovel can be concluded there is a possibility of kinship Dayak Bukit with Dayak Ngaju.